PREVENTION COMPLIANCE FACTOR ANALYSIS AND CONTROL OF NOSOCOMIAL INFECTIONS IN HOSPITALS - Anshori, Lalu Sofyan Jayadi; Saimi, Saimi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2024)
Nosocomial infections were infections that occurred in the hospital environment. A person was said to have a nosocomial infection if the infection occurred while undergoing treatment in the hospital. Nosocomial infections could occur in patients, nurses, doctors, and hospital workers or visitors. To prevent nosocomial infections, namely stopping the transmission method by increasing staff compliance and equipment maintenance procedures, decontamination, cleaning, and sterilization of the tools used, or high-level disinfection had to be considered before the equipment was used to carry out maintenance actions. If a nosocomial infection occurred, it impacted the length of treatment days due to comorbidities during hospitalization. Nosocomial infections had to be avoided and prevented in patient care in hospitals with a target of zero cases, one of the efforts was through staff compliance. Considering the risk of nosocomial infections, a compliance review of care workers was carried out. This study aimed to analyze compliance with the prevention and control of nosocomial infections in one hospital in West Nusa Tenggara Province. The method in this research was quantitative survey research with a cross-sectional approach. The research population was all nurses who worked in inpatient treatment rooms. By using a simple random sampling technique, a large sample of 50 nurses was obtained in this study. Chi-Square and Logistic Regression analysis were conducted using SPSS. The research results showed that there was a significant relationship between the factors education, knowledge, supervision, infrastructure, and management support on officer compliance. The dominant factor was found in the availability of infrastructure.